A Strain model for uPVC tube-confined concrete. Issue 1 (1st January 2021) - Abdulla, Nwzad Abduljabar
Abstract: The brittle response of concrete largely influences concrete deformation under axial load in the post-peak descending branch of the stress-strain curve. In this study, unplasticized polyvinyl chloride (uPVC) plastic tube used to confine concrete cylinders and improve the post-peak performance of specimens subjected to axial compression loads. Three experimental parameters, tube diameter, tube thickness, and H/D ratio, used to examine the mechanical behavior of eighteen uPVC tube confined short concrete columns. Test results show that when the outer diameter to thickness ratio (D/t) changed from 22 to 12.9, local buckling of the polymeric tube decreased, and the strain at peak stress was increased. So far, there is no model for predicting the strain of plastic tube confined concrete. The present test data was combined with more than 160 test data collected from the published literature to compile an experimental database. The number of test data for the strain of uPVC tube confined concrete reported in the literature is limited and less than those for strength. However, the assembled database was abundant enough to develop an ultimate condition model for the maximum axial strain accurately, based on the database. The developed model's accuracy was verified by comparing model predictions with twenty existing FRP-confined concrete models using three statistical indices. The distinguishing feature of the strain model includes several parameters on the concrete confined by the uPVC tube.